To Enhance the Operational Planning of an Independent Microgrid Using a Novel Combination of Demand Response Programs - Swami, Rekha; Gupta, Sunil Kumar (IAES Indonesian Section, 2024)
Providing electricity in rural or isolated areas involves high capital costs due to the cost of constructing transmission and distribution facilities. An independent Microgrid consisting of distributed generations (including both renewable and non-renewable energy sources) near the load could be an effective alternative. However, the unpredictability of renewable energy sources like wind and solar creates a problem in Microgrid operation, as there are instances when generation may not be enough to satisfy peak demand. Energy storage technology is generally employed to address this uncertainty. The Demand Response Program (DRP) is another technique that makes the Microgrid operation reliable and safe by lowering peak demand and switching it to low-load periods. This article addresses the short-term Unit Commitment Economic Dispatch (UCED) problem for an Independent Microgrid to reduce the overall operating costs using various DRPs. This paper presents a novel combination of DRP to enhance Microgrid’s operation and financial effectiveness and benefit its users. DRP modeling is done based on price elasticity and consumer benefit models. Mixed-integer nonlinear programming (MINLP) is used to formulate and solve the UCED problem in the GAMS software. 11-Bus Microgrid is considered for demonstration. According to the optimization results, implementation of TOU-RTP-CPPDLC DRPs reduces the operating cost by 13.68%, 13.31%, 17.16%, and 8.41%, respectively, with reduced load shedding. Consumers get benefits only in DLC-DRP. The proposed TOU+DLC-DRP combination reduces the operating costs by 13.48% with increased consumer benefits compared to DLC-DRP alone. Therefore, the proposed method is profitable for both the Microgrid operator and its users.